SOCIAL PRIORITIES OF FISCAL POLICY IN POST-CRISIS PERIOD - I. Lyutyy; D. Osetska (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка, 2014)
The article carried out a comprehensive study of the social priorities of fiscal policy in Ukraine. Efficiency of fiscal instruments in the system of state regulation of social processes in society. Defined the role of the budgetary impact on the social development of society.